Antimicrobial and cytotoxic activities of cerbera obollam seeds and leaves - Mohamad Fadzreen Mazlan (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
The ethanolic extractions from the parts (seeds and leaves) of Cerbera odollam were used in order to verify the antimicrobial activity and cytotoxicity by using different concentration of dilution prepared . The antimicrobial test was done to evaluate percentage of inhibition zone againts Fusarium sp. Colony growth on media with different concentration of extract dilution. The concentrations prepared were in 500 ppm, 1625 ppm, 2750 ppm, 3875 ppm, and 5000 ppm after all the concentration being selected by using One Factor sollution under Response Surface Methodology on Design of Expert software. The highest concentration of dilution of seeds and leaves at 5000 ppm were show highest percentage og inhibition zone, 86.67 % (seeds) and 66.7% (leaves).